IMPLEMENTING E-PALS AS A LEARNING STRATEGY TO INCREASE VOCABULARY KNOWLEDGE IN EFL STUDENTS - Astudillo Quiñónez, Miguel Alfredo; Miller, Kari; Maridueña, Jacqueline; Guevara , Pamela (Revista Inclusiones, 2021)
In Ecuador, there is a growing concern about the students’ English level, which has led educators to explore new methodological learning alternatives that include educational technological resources in order to achieve proficiency in this language. The objective of this experimental research was to demonstrate how the implementation of the learning strategy with E-PALS (friends in an electronic mean) helped students to acquire vocabulary. For this study, quantitative and qualitative data collection instruments were used: A Likert-type survey, a pre-test and a post-test. The post-test measured the amount of vocabulary use, vocabulary use in context, and spelling. Forty university students from an English class at Universidad Estatal de Milagro (Ecuador) participated in this study. The students were organized into learning pairs (E-PALS), who interacted on the technological tool Padlet. In this scheme, the study applied formative evaluation to verify the improvement of abilities and skills that helped the acquisition of new vocabulary. The SPSS application was used to process the data from which it was determined that the application of this pedagogical strategy increased the students’ knowledge of three elements related to vocabulary knowledge. They increased the number of words, reduced the errors in the use of words in context as well as decreased the number of errors of spelling in words. This led to an improvement in writing skills. The researchers concluded that the study benefits the English language educational community, as it helps to understand the relationship between, applying an active learning strategy and using technological resources to achieve vocabulary acquisition in a more efficient way.